The affective domain of generic competencies it is essential to educate integral professionals - González Navarro, María Gracia (2017)
In the educational model of the University of Concepcion, Chile, affective domain is developed during the third and fourth year of studies. This research presents theexperience of Biology career. In it, the strategy of reflexion is used to develop the affective domain of generic competencies with 13 students. Results show that there is a change in the way that students conceive generic competencies, from being a tool for good performance to be a fundamental part of professional training.